Management of faba bean gall in faba bean producing area of Eastern Amhara, Ethiopia - Hailemariam, Bogale Nigir; Melaku, Mulugeta Tilahun; Tagele, Setu Bazie; Kasaw, Tesfaye Desale; Bisewur, Eyeberu Abere; Ayalew, Abebe (Journal of Agriculture and Environment for International Development (JAEID), 2017)
Faba bean new disease (faba bean gall) (Olpidium viciae (Kusano) is the most destructive disease of faba bean ((Vicia faba L.) in Ethiopia, particularly in Amhara, Tigray and some part of Oromia region. This problem needs immediate sound management strategy to maximize faba bean productivity. A field study was carried out in Geregera and Jama during the 2013 and 2014 main crop season and Maybar watershed in 2014 to verify the fungicide to faba bean gall. The objective of this study was evaluating effective fungicides for the management of faba bean new disease. The treatments were baylaton in the form of seed dressing and foliar spray; mancozeb, redomil, chlorotalonin and cruzet in the form of foliar spray and apron star and theram used as a foliar spray and also untreated check used as a comparison. The result showed that significantly differ between treatments (p<0.05) on disease, agronomic and yield parameter in 2013 and 2014 at Geregera and Jama. Bayleton seed dressing significantly reduce the disease incidence, severity and area under disease progress curve (AUDPC) than other fungicides and untreated check. And significantly increase the yield and agronomic parameters. The analysis of variance indicated that bayleton seed dressing treated before six hours and bayleton seed dressing treated at the time of planting significantly reduce the disease incidence, severity and area under disease progress curve than mancozeb foliar spray, bayleton foliar spray and untreated check. And also bayleton seed dressing siginificantly increase the yield and pod per plant than mancozeb foliar spray, bayleton foliar spray and untreated check. In 2014 cropping season foliar sprayed fungicides and untreated check were recorded statistically non-significant variation between them, except yield and disease. Similarly, the verification result in t test (p<0.05) showed that bayleton seed dressing significantly reduce the disease incidence, severity and area under disease progress curve than other fungicides and untreated check. Therefore, bayleton wp 25% fungicide use as a seed treatment can reduced the disease pressure and protect faba bean from faba bean new disease (gall, koritim) (Olpidium viciae(Kusano).